Behaviors of ellipsoidal micro-particles within a two-beam optical levitator. (July 2017) - Petkov, T.; Yang, M.; Ren, K.F.; Pouligny, B.; Loudet, J.-C.
Abstract: The two-beam levitator (TBL) is a standard optical setup made of a couple of counter-propagating beams. Note worthily, TBLs allow the manipulation and trapping of particles at long working distances. While much experience has been accumulated in the trapping of single spherical particles in TBLs, the behaviors of asymmetrical particles turn out to be more complex, and even surprising. Here, we report observations with prolate ellipsoidal polystyrene particles, with varying aspect ratio and ratio of the two beam powers. Generalizing the earlier work by Mihiretie et al. in single beam geometries [JQSRT126, 61 (2013)], we observe that particles may be either static, or permanently oscillating, and that the two-beam geometry produces new particle responses: some of them are static, but non-symmetrical, while others correspond to new types of oscillations. A two-dimensional model based on ray-optics qualitatively accounts for these configurations and for the "primary" oscillations of the particles. Furthermore, levitation powers measured in the experiments are in fair agreement with those computed from GLMT (Generalized Lorentz Mie Theory), MLFMA (Multilevel Fast Multipole Algorithm) and approximate ray-optics methods. Highlights: Spheroids in two-laser beam geometry may stabilize in asymmetric configurations. Particles undergo different types of oscillations, in polar and azimuthal angles. Polar angle oscillations and asymmetric equilibriums are predicted by ray-optics. The basic levitation force decreases with particle aspect ratio. Experiments, simple ray optics and MLFMA calculations show similar tendencies.